Telephone-delivered Interpersonal Psychotherapy: a systematic review. (18th February 2023) - Miniati, Mario; Marzetti, Francesca; Palagini, Laura; Conversano, Ciro; Buccianelli, Beatrice; Marazziti, Donatella; Gemignani, Angelo
Abstract: Background: The aim of this paper is to review evidence on Interpersonal Psychotherapy (IPT) administered via telephone (IPT-T). Methods: We conducted a systematic review of studies published between January 1, 1990 and June 30, 2020, assessing the efficacy of IPT administered by phone, using PubMed. Results: Originally, we found 60 papers; the final selection led to 13 papers. Six studies were performed using a randomized clinical trial methodology (6/13, 46.2%), three were prospective open-label not randomized studies (3/13, 15.7%), three were pilot studies (3/13, 23.1%), and one was a feasibility/acceptance study (1/13, 7.7%). The number of subjects included in the studies ranged between 14 and 442 (mean: 140.0 ± 124.9), for a total of 1850 patients. The mean age of the enrolled subjects was 47.8 ± 9.3 years (range: 27.4-70.4). Thirty-four different instruments were utilized. Qualitative synthesis was conducted only on randomized controlled trials (RCTs), namely on six studies. RCTs were almost all of good quality (mean score/standard deviation of the RCT-Psychotherapy Quality Rating Scale omnibus rating: 5.6 ± 1.2 points; range: 3-7). Conclusions: IPT-T showed response rates similar to IPT administered in the usual way. Results are limited by small samples sizes, selection bias of the less severe depressed patients, and the heterogeneity of rating scales.